A forgiven Sinner? Robert Mugabe and the strained Catholic relations - Mwandayi, Canisius (LANGAA RPCIG, 2022)
In November 2017, a statement by the Zimbabwe Catholic Bishops Conference (ZCBC) thanked Robert Mugabe for the “good work” he had done as the President of Zimbabwe for 37 years but was quick to point out: “We forgive him for any shortcomings during his long tenure of office” (ZCBC, cited in Catholic Herald, 27 November 2017). Such a statement by the Catholic bishops summarises the controversy that surrounds Robert Mugabe. While he, at times, had good relations with the church, as seen in him receiving holy communion on a regular basis, as well as attending important church functions such as the burial of the late Pope John Paul 11 in 2005, there were darker moments as well when he came out vicious through word and action towards the same church he purported to be a member. Employing a socio-historical analysis, this chapter seeks to make a follow-up on Mugabe’s relations with the Catholic Church, highlighting in particular the strained moments. The chapter is propelled by the hand of forgiveness that was stretched towards Mugabe at the end of an era of his battle with the same church he claimed to be a member. The chapter argues that by extending a hand of forgiveness to Mugabe, the Catholic Church demonstrated what ‘true Christianity’ is all about as expatiated by C.S. Lewis (1949:182) who said: “To be a Christian means to forgive the inexcusable because God has forgiven the inexcusable in you.”